Activating temporary waqf and its mechanisms in social financing in alleviating the effects of Covid-19: applicable prospects in Malaysia - Ghalia, Bouhedda; Busari, Saheed Abdullahi; Yunus, Saidatolakma (2021)
Background: Waqf is considered as a voluntary Islamic socio-economic activity that combines the worldly interests which benefit the Waqf recipients and the endower by representing an act of worship of Muslims toward world rewards and ongoing rewards (sadaqah Jāriyah) in the hereafter. Moreover, there is an increasingly dire need among Muslims to cooperate and extend solidarity in all aspects of goodness especially in the period of emergency and natural disasters such as earthquakes, fires, wars, and plague. This is also important in the context of emergency conditions like Covid-19 and its economic effects on societies leading to increasing unemployment, poverty due to bankruptcy, and lockdown that has paralyzed many economic sectors. Objectives: This paper aims to explore the importance of employing the Temporary Waqf and its mechanisms based on the following discussion: First: How donation in the form of "temporary Waqf" encourages benevolent charity and expands solidarity and socio-economic cooperation the level of Individual private and government institutions. Second: the role of donation in the form of “temporary endowment” in regulating and standardizing charitable acts based on shariah and legal framework. Third: How benevolence loan (Qard Hasan) in the form of "temporary Waqf" can encourage and expands the scope of financial cooperation between people. Fourth: Explanation of some models for the application of the temporary Waqf based on Malaysian experience. Fifth: Proposing models to activate "temporary Waqf" for financing socio-economic activities purposes. Methodology: This study adopts inductive and analytical approaches in qualitative research. The study will conduct field research to explore the opinions of Waqf experts in Malaysia through online interviews.